Charles Dickens : the Writer and His Work. - Hardy, Barbara (Writers and Their Work Series., 1983)
The Writers and their Work series contains three essays on Dickens, an account of biographical and critical studies by K.J. Fielding and appreciations of the early and the late novels by Trevor Blount and Barbara Hardy respectively. Professor Hardy's present essay, the third Writers and their Work Special, combines a biographical introduction with a complete survey of the novels, sketches, and other prose works. Dickens originally learned his cr.